FDG PET/CT in Detection of Metastatic Involvement of Heart and Treatment Monitoring in Non-Hodgkin′s Lymphoma - Kanhaiyalal Agrawal; Bhagwant Mittal; Kuruva Manohar; Raghava Kashyap; Anish Bhattacharya; Subhash Varma (World Journal of Nuclear Medicine)
Cardiac metastasis occurs in up to a quarter of patients with metastatic cancer and is seen most commonly in melanoma and lymphoma. Metastatic involvement of the heart and pericardium may go unrecognized until autopsy. We describe a patient of non-Hodgkin′s lymphoma detected to have involvement of right atrium on F-18 FDG PET/CT and monitoring of response to chemotherapy.